التعاون الدولي في ظل النظام الأساسي للمحكمة الجنائية الدولية - عتيق علي (My University, 2024)
Abstract International crime, as one of the byproducts of the policy of international domination and the accompanyingarmedconflicts, poses a seriousthreat to the peace and security of the international community, especially in light of the widespreadphenomenon of impunity, thereforeitwasnecessary to put an end to thisphenomenon by punishing the perpetrators of those crimes and putting thembehind prison bars.in order to achievethis, manyjudicial bodies have been established at the international level, headed by the International Criminal Court, whichis the first permanent international judicial body concernedwithcombating the mostserious international crimes and pursuingtheirperpetratorscriminally. In order to achieve the mission of the Court in confronting international crimes, itsstatuteestablished a number of mechanisms and provisions, international cooperationbeing one of the most important, as activating international cooperationwith the International Criminal Court requiresserious international action based on the commitment of the states parties to the provisions of the court’sstatute, in addition to a general international commitment to the rules of the court. International humanitarianlaw and the variouscustomaryrules of international law, and applyingthoserules in good faith as stipulated in the provisions of international agreements. The issue of international cooperationwith the court alwaysremainshostage to the politicalwill of states and the extent of theircommitment to thoserules. International cooperationwith the International Criminal Court faces many challenges, which must beaddressed by searching for appropriatemechanismsthat help activate international cooperation and achieve the established goals of the International Criminal Court stipulated in itsstatute. ----------- Résumé de la thèse La criminalité internationale, en tant que sous-produit de la politique de domination internationale et des conflits armés qui l'accompagnent, constitue une grave menace pour la paix et la sécurité de la communauté internationale, en particulier à la lumière du phénomène généralisé de l'impunité, et il était donc nécessaire de mettre un terme à ce phénomène en punissant les auteurs de ces crimes bars. Pour y parvenir, de nombreux organes judiciaires ont été créés au niveau international, dirigé par la Cour pénale internationale, qui est le premier organe judiciaire international permanent chargé de lutter contre les crimes internationaux les plus graves et de poursuivre pénalement leurs auteurs. La coopération internationale est l'une des plus importantes, car l'activation de la coopération internationale avec la Cour pénale internationale nécessite un travail international sérieux fondé sur l'engagement des États parties aux dispositions du statut de la cour, en plus d'un engagement international général aux règles du droit international humanitaire et diverses règles coutumières du droit international, et l'application de ces règles de bonne foi comme stipulée par les dispositions des accords internationaux. La question de la coopération internationale avec la Cour reste toujours l'otage de la volonté politique des États et de l'étendue de leur attachement à ces règles. La coopération internationale avec la Cour pénale internationale est confrontée à de nombreux défis, qui doivent être relevés en recherchant des mécanismes appropriés qui aident à activer la coopération internationale et à atteindre les objectifs de la Cour pénale internationale stipulés dans son statut. ------------ تشكل الجريمة الدولية كأحد إفرازات سياسة الهيمنةالدولية وما يصحبها من نزاعات مسلحة خطرا جسيما على سلم وأمن المجتمع الدولي خاصة في ظل تفشي ظاهرة الإفلات من العقاب، وبالتالي توجب وضع حد لهذه الظاهر من خلال معاقبة مرتكبي تلك الجرائم ووضعهم خلف قضبان السجون، وحتى يتسنى تحقيق ذلك فقد تم إنشاء العديد من الأجهزة القضائية على المستوى الدولي، كان على رأس تلك الأجهزة المحكمة الجنائية الدولية التي تعد أول هيئة قضائية دولية دائمة تعنى بمكافحة أخطر الجرائم الدولية ومتابعة مرتكبيها جنائيا. حتى يتم تحقيق رسالة المحكمة في التصدي للجرائم الدولية وضع نظامها الأساسي جملة من الاليات والبنود يعد التعاون الدولي من أهمها، حيث يتطلب تفعيل التعاون الدولي مع المحكمة الجنائية الدولية عمل دولي جاد مبني على التزام الدول الأطراف ببنود نظام المحكمة الأساسي، بالإضافة إلى إلتزامدولي عام بقواعد القانون الدولي الإنساني ومختلف القواعد العرفية للقانون الدولي،وتطبيق تلك القواعد بحسن نية مثلما نصت عليه بنود الاتفاقيات الدولية، فمسألة التعاون الدولي مع المحكمة تبقى دائما رهينة الإرادة السياسية للدول ومدى التزامها بتلك القواعد. حيث تواجه التعاون الدولي مع المحكمة الجنائية الدولية العديد من التحديات، التي يتوجب التصدي لها من خلال البحث عن الاليات المناسبة التي تساعد على تفعيل التعاون الدولي، وتحقيق الأهداف المسطرة للمحكمة الجنائية الدولية المنصوص عليها في نظامها الأساسي.